Aplicación del proceso enfermero a la práctica asistencial en el caso clínico de neumonía, síndrome bronco-obstructivo. - Masache Novillo, Yessenia del Cisne (2013)
The objective of international NANDA, is to strengthen the development of the infirmary knowledge. Presently study, was applied the stages of the process male nurse, starting from the valuation using the 11 functional Patterns of Health of Marjory Gordon; the diagnosis settled down using the taxonomy International NANDA and the linking NOC and NIC that guided the determination and execution of infirmary actions. The study was descriptive, prospective, qualitative. The methodology was applied to a clinical case in a boy of 2 months of age that I enter to the service of Pediatrics with Diagnosis Medical Pneumonia, Rough Obstructive Syndrome. It was obtained as results, diagnostic male nurses NANDA I: Breathing ineffective pattern related with syndrome of hiccup ventilation, manifested by taquipnea. (Code 00032) (Boy), ineffective Cleaning of the air roads related with excessive mucosity manifested by cough inefectiva. (Code 00031) (Boy), I Deteriorate of the maintenance of the home related with economic insufficient resources, manifested for on it loads of the members of the family. (Code 00098) (Family), Estrés for overload related with inadequate resources, manifested by expressed sensation of tension. (Code 00177) (Mother); NOC: Breathing state: ventilation. (Código0415), State breathing permeability of the breathing roads. (Code 0410), sure Atmosphere of the home. (Code 1910), estrés Level. (Código1212), same that guided the infirmary actions. Finally according to the valuation of the results by means of the scale of Likert, the indicators that are still in risk are: Sure atmosphere of the home (Code 1910) with a risk of Substantially appropriate and estrés (Code 1212) Level with a light Risk. KEYWORDS : Bronco obstructive syndrome , Nanda , NIC, NOC , rating .